Penggunaan Bahasa Indonesia Mahasiswa Program Studi Pendidikan Guru Madrasah Ibtidaiyah UIN Raden Fatah Palembang - Fatmawaty, Fatmawaty (Indo-MathEdu Intellectuals Journal, 2025)
Indonesian, as both a national language and an academic language, demands clarity, precision, and adherence to syntactic, morphological, and orthographic rules. However, in practice, many student writings deviate from these linguistic norms. This study aims to identify and analyze forms of linguistic anomalies in the writings of students in the Madrasah Ibtidaiyah Teacher Education (PGMI) Program, particularly in the use of written Indonesian. This research employs a descriptive qualitative approach with content analysis techniques applied to thesis proposal documents. In addition to documentation, data were collected through direct speech observation and in-depth interviews. The subjects of this literature review consist of various written sources such as books, journals, and scientific documents. Data analysis uses content analysis to interpret information systematically and thoroughly. The results reveal that the most common anomalies include ineffective sentences, nonstandard word usage, and errors in spelling and punctuation. Contributing factors include limited academic literacy, the influence of spoken language and social media, and the lack of continuous practice in formal writing. This study highlights the importance of strengthening language learning and scientific writing training to improve the academic communication skills of PGMI students.